Working Characteristics of a Rotary Booster-driven Loop Cooling Unit - Li Shaocong; Ma Guoyuan; Xue Lianzheng; Zhou Feng (Zhileng xuebao)
Free cooling is widely applied in data centers as a promising technology for energy conservation. A loop cooling unit driven by a miniature rotary booster for free cooling was developed for a small data center. In this study, compared with air conditioners and pump-driven loop heat-pipe units, the booster-driven loop cooling unit consumed lower power and had a higher energy efficiency ratio (EER). An improved rotary booster with a small pressure ratio was adopted in the rotary booster-driven loop cooling unit. The results indicate that with the increase in the indoor and outdoor temperature difference (ΔT), the unit cooling capacity and EER first increased and then decreased. When ΔT was 25 ?C, the cooling capacity reached 17.7 kW, and the EER was 15.2. With the increase in ΔT, the power of the unit exhibited a downward trend all the time. When ΔT was 25 ?C, the power of the unit reached 1.16 kW. The thermal performance was compared with that of the pump-driven loop heat-pipe unit. When ΔT was 25 and 10 ?C, the EER values of the rotary booster-driven loop cooling unit were 25.5% and 104.7% higher than those of the pump-driven loop heat-pipe unit, respectively.